2016
DOI: 10.1021/acscatal.5b02001
|View full text |Cite
|
Sign up to set email alerts
|

The Choice Is Yours: Using Liquid-Assisted Grinding To Choose between Products in the Palladium-Catalyzed Dimerization of Terminal Alkynes

Abstract: Herein, we report on the dimerization of terminal alkynes using various palladium catalysts under solvent-free mechanochemical conditions. When tetrakis­(triphenylphosphine)­palladium(0) was employed as the catalyst, we observed the 1,3-butadiyne as the major product. However, when we employed bis­(triphenylphosphine)­palladium­(II) dichloride as the catalyst, we observed the trans-enyne as the major product. When we used a polymer-supported bis­(triphenylphosphine)­palladium­(II) dichloride catalyst under liq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(42 citation statements)
references
References 69 publications
0
42
0
Order By: Relevance
“…However, the choice of the suitable polymer for a specific transformation was not trivial: the ‘fine tuning’ of the physical state of the system was also related to specific physical aspects also connected to the intrinsic properties of the polymer. In addition, PEG polymers were demonstrated as a valid eco-friendly and safe alternative to classic solvents used in liquid-assisted-grinding procedures (LAG) [1822] due to their low melting point (45–60 °C), enabling their use as melt during grinding, low toxicity and low vapour pressure, reducing the risk of explosions or overpressure that might be encountered on large scale LAG-procedures.…”
Section: Resultsmentioning
confidence: 99%
“…However, the choice of the suitable polymer for a specific transformation was not trivial: the ‘fine tuning’ of the physical state of the system was also related to specific physical aspects also connected to the intrinsic properties of the polymer. In addition, PEG polymers were demonstrated as a valid eco-friendly and safe alternative to classic solvents used in liquid-assisted-grinding procedures (LAG) [1822] due to their low melting point (45–60 °C), enabling their use as melt during grinding, low toxicity and low vapour pressure, reducing the risk of explosions or overpressure that might be encountered on large scale LAG-procedures.…”
Section: Resultsmentioning
confidence: 99%
“…[16,17] Numerous examples of processes in which, by applying mechanicalg rinding, the use of solvent has been eliminated,t he time of the reaction was shortened, and energy consumption was substantially reduced are reported in the literature. Intriguingly,i ns ome cases, the chemical structures of the products formed under mechanochemical conditions are substantially differentf rom these under classical solutionc onditions [20][21] and forbidden transformations take place. Intriguingly,i ns ome cases, the chemical structures of the products formed under mechanochemical conditions are substantially differentf rom these under classical solutionc onditions [20][21] and forbidden transformations take place.…”
Section: Introductionmentioning
confidence: 97%
“…All these elegant findings intrigue us to preconceive that the participation of LAGs in metal‐catalyzed asymmetric reactions might lead to highly active chiral metal complexes through non‐covalent bond interaction and provide efficient control of both reactivity and enantioselectivity (Scheme , d). While there are previous examples where the chemo‐selectivity, rate, kinetics or products of a reaction have been changed, LAGs enabled enantio‐control is, to the best of our knowledge, unprecedented.…”
Section: Introductionmentioning
confidence: 99%
“…Liquid‐assisted grinding (LAG) has emerged as an extension of traditional solvent‐free mechanochemical techniques by using a small amount of liquid as an additive to enhance or control reactivity . Albeit studies have shown its effectiveness in both inorganic and organic syntheses, the mechanism of their action is generally unclear with recent studies pointing to some physical factors such as dissolution, molecular mobility, and liquid polarity . Alternative to physical effects, the liquid‐assisted grinding solvent (LAGs) can actively participate through chemical interactions as catalysts, bases, and other specific interactions [9k–l,9 ° –p] to improve the reactivity in organic transformations.…”
Section: Introductionmentioning
confidence: 99%